2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2018
DOI: 10.1109/embc.2018.8512802
|View full text |Cite
|
Sign up to set email alerts
|

Altered Connectivity in Autistic Adults during Complex Facial Emotion Recognition: A Study of EEG Imaginary Coherence

Abstract: Difficulties in Facial Emotion Recognition (FER) are commonly associated with individuals diagnosed with Autism Spectrum Disorder (ASD). However, the mechanisms underlying these impairments remain inconclusive. While atypical cortical connectivity has been observed in autistic individuals, there is a paucity of investigation during cognitive tasks such as FER. It is possible that atypical cortical connectivity may underlie FER impairments in this population. Electroencephalography (EEG) Imaginary Coherence was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Similarly, a preference for high-pass frequency features has been found in FER studies previously (52), with this preference consistent with altered cognitive style hypotheses (44). Decreased connectivity in the lower EEG frequency bands was also reported earlier on a similar sample using imaginary part of coherency (19), and a recent review found that lower connectivity seemed to be dominant in the lower frequencies while higher and lower connectivity appeared to be dominant in the higher frequency bands (11). An absence of the modulation of theta-band coherence during an emotion recognition task in autistic children compared to non-autistic children was found (53), with the severity of social impairment found to be related to the absence of cortical connectivity modulation of the band.…”
Section: Shift In Emotional Processing To Higher Frequency Bands In A...supporting
confidence: 85%
See 3 more Smart Citations
“…Similarly, a preference for high-pass frequency features has been found in FER studies previously (52), with this preference consistent with altered cognitive style hypotheses (44). Decreased connectivity in the lower EEG frequency bands was also reported earlier on a similar sample using imaginary part of coherency (19), and a recent review found that lower connectivity seemed to be dominant in the lower frequencies while higher and lower connectivity appeared to be dominant in the higher frequency bands (11). An absence of the modulation of theta-band coherence during an emotion recognition task in autistic children compared to non-autistic children was found (53), with the severity of social impairment found to be related to the absence of cortical connectivity modulation of the band.…”
Section: Shift In Emotional Processing To Higher Frequency Bands In A...supporting
confidence: 85%
“…The experimental design is the same as reported elsewhere ( 19 , 22 ). Video stimuli from the Cambridge Mind Reading Face-Voice Battery ( 25 ) of actors expressing complex emotions were used in this study to evaluate FER.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os resultados mostraram que a máxima taxa de reconhecimento alcançada foi de 91,9%. A resposta às emoções faciais também foram usadas por Black et al (2018) para calcular a parte imaginária da coerência. Os resultados indicaram que adultos com TEA demonstraram coerência reduzida inter-hemisférios de curto e longo alcance.…”
Section: Conectividade Cerebralunclassified